Contemporary Fiqh Studies on Gender Equality: A Study of Women's Careers in the Modern Era - Yasmin Raihanah Zaviril; Adrian Seputro Ginting (Jurnal Cendikia ISNU SU, 2025)
The issue of gender equality in the world of work is one of the contemporary issues that continues to be a concern in Islamic discourse. This article aims to examine fiqh's view on women's involvement in the career world and the  limitations of shari'i that accompany it. Using a normative-theological approach, this article examines the postulates from the Qur'an, Hadith, and the views of classical and contemporary scholars on the role of women in the public sphere. The results of the study show that Islam in principle does not prohibit women from working as long as they maintain moral values, domestic obligations, and do not violate the provisions of sharia. This article also highlights the importance of contextually reinterpreting religious texts in order to be able to respond to the challenges of the times without overriding the basic principles of Islam. The conclusion of this study emphasizes the need  for equitable equality  between men and women in access to employment, as well as the protection of women's rights as individuals and part of the family and society.